Pengaruh Pajak dan Pemanfaatan Tax Haven pada Transfer Pricing - Devi, Ni Putu Ayu Liony Krishna; Noviari, Naniek (E-Jurnal Akuntansi, 2022)
Transfer pricing is the determination of prices in transactions between parties that have a special relationship. Transfer pricing carried out by the company in order to minimize the tax burden paid by the company by utilizing transactions with related parties. This study aims to examine the effect of taxes and the use of tax havens on transfer pricing. This research was conducted on mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Determination of the number of samples in this study using a purposive sampling technique with three criterias, namely mining sector companies listed on the IDX that publish an annual report, earn profits, and have transactions with related parties in 2016-2020. Based on these criteria, the number of samples used in this study was 15 samples of companies with 75 observational data. Data were analyzed using multiple linear regression analysis. The results of this study indicate that taxes have no effect on transfer pricing, while the use of tax havens has a positive effect on transfer pricing.    Keywords: Tax; Tax Haven; Transfer Pricing.